PENGARUH IMPLEMENTASI KEBIJAKAN TERHADAP KUALITAS PELAYANAN BANDUNG INTEGRATED MANPOWER MANAGEMENT APPLICATION - Tamara, Cindi; Suhara, Ero (Jurnal Sosial Politik Unla, 2023)
The problem in this research is the low quality of service in the Employment Application, namely the Bandung Integrated Manpower Management Application (BIMMA) which is implemented by the Bandung City Employment Service. According to the researcher's assumption, the low quality of service in this application is still influenced by the Policy Implementation variable. Based on these problems, the problem formulation proposed is: "How big is the influence of policy implementation on the quality of service in the Bandung Integrated Manpower Management Application." The theory used in this research is Policy Implementation as a Variable(X) from Edward III in Agustino, with dimensions: Communication, Resources, Disposition and Bureaucratic structure. Meanwhile, the variable (Y) Service Quality uses the theoretical approach of Parasuraman, Zeithaml, and Berry quoted by Adam with the dimensions of Physical Evidence, Reliability, Responsiveness, Guarantee and Attention. Meanwhile, the hypothesis proposed by the researcher is 52.08% and there are another influences that were not researched amounting to 42,02% regarding control. The research method used is quantitative using simple linear regression and based on the research results, it shows that there is a strong and unidirectional relationship with the influence of policy implementation on service quality in the Bandung Integrated Manpower Management Application. Thus, the hypothesis proposed in this research was tested empirically.